Psammomatoid variant of juvenile ossifying fibroma involving mandible: A rare case report - Kumar, Saurabh (Contemp Clin Dent, 2015)
The term juvenile ossifying fibroma (JOF) is used in literature in naming two microscopically distinct fibro-osseous lesions of the craniofacial skeleton. One is characterized by small uniform spherical ossicles resembling psammoma bodies (psammomatoid JOF [PsJOF]). The other is distinguished by trabeculae of fibrillary osteoid and woven bone (trabecular JOF). Psammomatoid ossifying fibromas represent a unique subset of fibro-osseous lesions of the craniofacial region. PsJOF has been distinguished because of its location, clinical behavior, and age of occurrence. They have distinctive histomorphologic features and a tendency toward locally aggressive behavior, including invasion and destruction of adjacent anatomic structures. It is generally seen in the younger age group, and the most common site is paranasal sinuses, orbits, and frontoethmoidal complex. We report a case of JPOF involving mandible which is rarely been described in literature. An insight into the radiographic progression of this rare entity along with the clinical feature and surgical management is discussed.